The impacts of investment in internal audit functions on the going concern opinion for financially distressed firms - Fazlin Erwinaz Hassan,; Amirul Hafiz Mohd Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2020)
We investigate the effects of internal audit investments on financially distressed firms in Malaysia. Specifically, we examine the impacts of internal audit investments on these firms’ going concern opinion. We argue that higher internal audit investments expedite these firms’ recoverability by improving their controls and operations. The assurance and consulting activities provided by internal auditors enable these firms to mitigate the material uncertainty of the going concern opinions issued by external auditors. To examine such relationship, we chose 137 firm-year observations of Malaysian financially distressed firms listed on Bursa Malaysia from 2016 to 2018. We ran a logistic regression analysis and found that internal audit investments are negatively and significantly associated with the going concern opinions reported by an external auditor. This result suggests that high internal audit investments reduce the likelihood for an external auditor to issue a going concern opinion. As stated in ISA 570, if recovery plans have no material uncertainty and are sufficient to mitigate the going concern problem (which is argued to be assisted by the internal audit function of the firm), then an external auditor can issue a clean audit report even for firms that are in financial distress. Evidence from this study contributes to our understanding of the importance of investments in internal audit functions and highlights that the assurance and consultation from internal auditors can ensure a careful monitoring of the strategies and operations of firms.